Learn and Adapt, or Perish: The Case of the F35 Lightning II. Issue 7 (August 2022) - Gerrits, Lasse; Marks, Peter
We assess to what extent a (co)evolutionary macro level approach enhances our understanding of learning in governance processes. We ask the question: in what ways do actors learn to improve their chances of long-term survival in complex governance processes? We deploy a model of collective decision making moulded upon fitness landscapes to analyze a longitudinal case study of collective (political and administrative) decision making, namely the process of developing and acquiring the F35 Lightning II fighter jet. The study demonstrates that actors learn how to ensure survival over time but create a failing megaproject in the process.